Two new species of Podonomus (Diptera: Chironomidae: Podonominae) of the Brundin’s decarthrus group from Ventania system, Argentina - Siri, Augusto; Donato, Mariano (Zootaxa, 2012)
The descriptions and illustrations of two new species of Podonomus, P. tehuelche and P. quinquesetosus are presented. Both species belong to the Brundin’s decarthrus group and were collected in an "orogenic island", representing the first record of a named Podonomus species from Argentina outside the Andean-Patagonian region. Immatures and adults were collected at relatively low altitude for the genus (500 to 800 m a.s.l.). A key for the South American male adults and pupae of the decarthrus group is presented.